Beyond the silence - Peterson, Tracie; Woodhouse, Kimberley, 1973- (Bethany House, 2016)
Lillian Porter is thrilled to accept a nanny position out west, until she arrives and hears troubling rumors that her employer caused his wife's death. But the accusation doesn't align with the man she comes to know--and love. When Woody is arrested on suspicion of attacking his housekeeper, can Lillian find the truth in time to save them both from tragedy?